Fitness, Fatness, Physical Activity, and Autonomic Function in Midlife. Issue 12 (December 2017) - KIVINIEMI, ANTTI M.; PERKIÖMÄKI, NELLI; AUVINEN, JUHA; NIEMELÄ, MAISA; TAMMELIN, TUIJA; PUUKKA, KATRI; RUOKONEN, AIMO; KEINÄNEN-KIUKAANNIEMI, SIRKKA; TULPPO, MIKKO P.; JÄRVELIN, MARJO-RIITTA; JÄMSÄ, TIMO; HUIKURI, HEIKKI V.; et al.
ABSTRACT: Purpose: Although low cardiorespiratory fitness (CRF), physical inactivity, and obesity are associated with impaired autonomic function, they are also extensively interrelated. The present study aimed to assess the extent to which they contribute to autonomic function independently of each other. Methods: At the age of 46 yr, 1383 men and 1761 women without cardiorespiratory diseases and diabetes underwent assessments of vagally mediated heart rate (HR) variability (root mean square of successive differences in R-R interval (rMMSD)), peak HR during a submaximal step test (CRF), and 60-s HR recovery (HRR). Moderate-to-vigorous physical activity (MVPA; ≥3.5 METs, 2 wk) was measured by wrist-worn accelerometer and body fat percentage (Fat%) by bioimpedance. Results: In men, CRF and Fat% were significantly associated with higher rMSSD (standardized β = 0.31 and −0.16) and HRR ( β = 0.19 and −0.18), whereas higher MVPA was linked with higher HRR ( β = 0.13) when including CRF, MVPA, and Fat% in the initial regression. After adjustments for other lifestyle and cardiometabolic factors, CRF remained significantly associated with rMMSD ( β = 0.24) and HRR ( β = 0.14), as did MVPA with HRR ( β = 0.11). In women, CRF was associated with rMSSD ( β = 0.23) and HRR ( β = 0.15), and MVPA ( β = 0.17) and Fat% ( β = −0.07) with HRR, when CRF, MVPA, and Fat% were adjusted for each other. After further adjustments, CRF remained a significant determinant of rMSSD ( β = 0.20) and HRR ( β = 0.13), as did MVPA with HRR ( β = 0.15). The final models explained 23% and 21% of variation in rMSSD and HRR in men, and 10% and 12% in women, respectively. Conclusions: CRF was a more important determinant of cardiac autonomic function than MVPA and body fat. Furthermore, MVPA but not body fat was independently associated with cardiac autonomic function in both men and women. Abstract : Supplemental digital content is available in the text.